Anti-angiogenic effect of tamoxifen combined with epirubicin in breast cancer patients. - Mele, T; Generali, D; Fox, S; Brizzi, M; Bersiga, A; Milani, M; Allevi, G; Bonardi, S; Aguggini, S; Volante, M; Dogliotti, L; Bottini, A; et al. (2010)
Vascular endothelial growth factor A (VEGF-A) and vascular endothelial growth factor receptor 2 (VEGFR2) are the key factors mediating neo-vascularization. They are often coexpressed in breast cancer. Sex steroids may stimulate angiogenesis via the estrogen receptor (ER) pathway. We investigated to compare the effects of the addition of tamoxifen to epirubicin versus epirubicin alone on VEGF and VEGFR2 expression in breast cancer patients. The expression of VEGF and VEGFR2 was assessed on tissue microarray by immunohistochemistry at baseline conditions and after treatments in the case of 191 patients with T2-4 N0-1 breast cancer enrolled in a randomized trial comparing four cycles of single agent epirubicin versus epirubicin plus tamoxifen as primary systemic treatment. Epirubicin alone failed to induce changes in VEGF expression (P = 0.54), while the addition of tamoxifen to epirubicin resulted in a significant reduction in VEGF expression (P < 0.001). As a consequence, baseline VEGF had a negative prognostic role in patients who received epirubicin alone but not in patients receiving epirubicin plus tamoxifen (interaction test P < 0.05). VEGFR2 expression increased at residual tumor histology in both treatment arms, with a lesser extent in patients receiving tamoxifen plus epirubicin. Decrease in VEGFR2 expression was significantly associated with response rate (P = 0.02). The addition of tamoxifen to epirubicin resulted in a suppression of a key angiogenic pathway. These data suggest a potential synergism of these two drugs.